Specificity of Lepidelphax pistiae (Hemiptera: Delphacidae) to Pistia stratiotes (Araceae) - Cabrera Walsh, Guillermo José (2014)
The delphacid Lepidelphax pistiae was found on water lettuce in Argentina. Nymphs and adults did not survive past seven days on 29 species of test plants, and no progeny were produced. In contrast, survival and reproduction were high on water lettuce. Results suggest that L. pistiae is monospecific to water lettuce.